The Gulf of Guinea goby‐shrimp symbiosis and a review of goby‐thalassinidean associations - Wirtz, Peter (2009)
An undescribed species of the family Gobiidae shares the burrows of the axiid shrimp Axiopsis serratifrons at São Tomé and Príncipe (central eastern Atlantic). In contrast to similar associations of gobiid fishes with alpheid shrimps in the Indo-Pacific and the western Atlantic (where the goby serves as a sentinel for the crustacean and the shrimp leaves the burrow only if the goby remains at the burrow entrance), the axiid appears to completely ignore the goby, which rests near the opening of the burrow. Facultative and obligatory associations of gobies with thalassinidean shrimps are reviewed.